1994
DOI: 10.1084/jem.179.1.101
|View full text |Cite
|
Sign up to set email alerts
|

The human immunodeficiency virus-1 nef gene product: a positive factor for viral infection and replication in primary lymphocytes and macrophages.

Abstract: SummaryConsiderable controversy and uncertainty have surrounded the biological function of the Human Immunodeficiency Virus (HIV)-I nef gene product. Initial studies suggested that this early, nonstructural viral protein functioned as a negative regulatory factor; thus, it was proposed to play a role in establishing or maintaining viral latency. In contrast, studies in Simian Immunodeficiency Virus (SIV)mac-infected rhesus monkeys have suggested that Nef is not a negative factor but rather plays a central role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
385
2
4

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(415 citation statements)
references
References 49 publications
(68 reference statements)
23
385
2
4
Order By: Relevance
“…The difference in infectivity between Nef+ and Nef− virions is more pronounced following infection of freshly isolated T cells which are stimulated after infection than it is following infection of T cells which are activated before infection. 32 Consistent with this, we observed a greater decrease in transduction efficiency with deleted vectors in freshly isolated T cells compared with cells that were pre-stimulated. Hence, the absence of Nef may play a role in the decreased transduction efficiency we observed with deleted vectors in T lymphocytes.…”
Section: Discussionsupporting
confidence: 85%
“…The difference in infectivity between Nef+ and Nef− virions is more pronounced following infection of freshly isolated T cells which are stimulated after infection than it is following infection of T cells which are activated before infection. 32 Consistent with this, we observed a greater decrease in transduction efficiency with deleted vectors in freshly isolated T cells compared with cells that were pre-stimulated. Hence, the absence of Nef may play a role in the decreased transduction efficiency we observed with deleted vectors in T lymphocytes.…”
Section: Discussionsupporting
confidence: 85%
“…R5-tropic clones JR-CSF and nef-defective JR-CSF⌬X were gifts from Jerome Zack (33). The YU2b chimera, containing the BssHII-XhoI fragment of YU2 inserted into the equivalent sites of R7, and YU2b⌬N, containing an end-filled XhoI site within the Nef gene, were gifts from M. Feinberg and were described previously (47).…”
Section: Methodsmentioning
confidence: 99%
“…The absence of high viral loads associated with Nef-defective virus infection suggests that Nef promotes virus replication in vivo. In vitro, Nef enhances HIV-1 replication in primary T lymphocytes and macrophages (24,47,63,65). Although the precise mechanism by which Nef enhances replication in primary T lymphocytes is unknown, we and others have reported that CD4 downregulation by Nef is strongly linked to HIV-1 replication in primary T lymphocytes, peripheral blood mononuclear cells (PBMC), and tonsillar histocultures (29,43).…”
mentioning
confidence: 96%
“…Nef also has a positive effect on the infectivity of virions (18,19), a function which remains mechanistically unexplained. Although the ability to down-regulate CD4 can contribute to the effect of Nef on infectivity (20), this activity is visible by using CD4-negative producer cells and was shown to be independent from other Nef effects (18,(21)(22)(23), it requires its expression in virus-producing cells and is manifested at an early step of the infection process of target cells (18,22,(24)(25)(26).…”
mentioning
confidence: 99%